Valuing Modularity as a Real Option - Gamba, Andrea; Fusari, Nicola (Management Science, 2009)
We provide a general valuation approach for capital budgeting decisions involving the modularization in the design of a system. Within the framework developed by Baldwin and Clark (Baldwin, C. Y., K. B. Clark. 2000. Design Rules: The Power of Modularity. MIT Press, Cambridge, MA), we implement a valuation approach using a numerical procedure based on the least-squares Monte Carlo method proposed by Longstaff and Schwartz (Longstaff, F. A., E. S. Schwartz. 2001. Valuing American options by simulation: A simple least-squares approach. Rev. Financial Stud. 14(1) 113–147). The approach is accurate, general, and flexible.